Addressing the Menace of Child Marriage in Nigeria through the Law (2014)
Child marriage creates problems for the girl-child. It is a problem that affects the anatomy of the child and it diminishes global development efforts focused on creating more educated, healthier and economically stable populations. It is a topical issue that has pervaded our society. Child marriage occurs most often in poor rural communities. It often occurs where parents arrange their daughter’s marriage unknown to the girl, that is, without the consent or the knowledge of the child. This simply means that the girl-child may be at home playing with her siblings and suddenly, she is married off and sent to live in another village with her husband and his family—strangers, essentially. She is pulled out of school. She is separated from her peers. Once the girl-child is married, she is more likely to be a victim of domestic violence and suffer health complications associated with early sexual activity and childbearing.This article therefore examines the phenomenon of child marriages in Nigeria, its causes and effects and how such can be addressed through the law.